Peran Manajemen Pemasaran Pada Aplikasi Quipper Sebagai Media Pembelajaran Siswa: Studi Literatur - Siti Zakiyya Nur Aulia Kurniawan; Resya Dwi Marselina; Rismayanti Dewi (Journal of Management and Creative Business, 2024)
Industrial relations disputes in Indonesia are commonly experienced by industrial relations actors. Industrial relations mediators have duties and responsibilities as labor mediators. The purpose of the research is to understand the role of the mediator when resolving industrial relations disputes at PT Dymatic Chemicals Indonesia, identify factors that influence the effectiveness of the mediator, and provide suggestions to improve the dispute resolution process. The research method used is a qualitative method of data technique through simak catat interview. The result of the discussion of this research is that the role of mediators in the company in resolving labor disputes plays a very important role. Mediators of PT Dymatic Chemicals Indonesia in resolving workers' problems are usually done by mediation.